Badan Usaha Milik Desa Dan Keberlanjutan Ekonomi Pedesaan Di Kabupaten Berau (Pendekatan Dynamic Capabilities Theory) - Endah Susanti (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
BUMDes (Village-Owned Enterprises) are an important instrument in local economic development because they utilize the potential of resources and human resources in the village to improve community welfare. BUMDes play a role in driving the village economy, increasing community income, and supporting sustainable village development. This study aims to understand the reality of the existence of BUMDes and its impact on the sustainability of the village economy. This study focuses on understanding the perspective of village business entities and asking whether these business entities are able to improve the village economy by increasing the capacity of BUMDes that support village sustainability and are analyzed using the dynamic capability theory approach. This study uses a qualitative approach with informants from village-owned business entity administrators and villagers who run small businesses in rural Berau Regency. The results of the analysis of the four components of dynamic capabilities found that BUMDes in rural areas of Berau Regency have not been able to recognize the potential of the village environment that can be developed due to their inability to capture opportunities to develop the market; BUMDes in Berau Regency often operate with limited resources, both in terms of capital, skills, or support from the local government; Limited digital infrastructure and low digital literacy in remote rural areas of Berau Regency; and weak managerial capabilities of BUMdes administrators. Dynamic BUMdes that follows developments in the business world is the key to build rural economic sustainability.